The discursive identities of Hamas and Israel in British newspapers: a socio-cognitive analysis - Al-Ramahi, Raed Awad Omar; Radzuwan Ab Rashid (Penerbit Universiti Kebangsaan Malaysia, 2024)
This article investigates the discursive construction of identities in media discourse, focusing on how British newspapers portrayed Israel and Hamas following October 7th. This study, grounded in van Dijk's socio-cognitive frameworks, used a thematic approach to analyse a dataset of 150 news story headlines from 11 British newspapers. The data collection period extended from October 7th to October 15th, 2023. Data analysis reveals that headlines frequently employ specific discursive strategies to depict Israel as a victim and Hamas as a terrorist organisation. The strategies include polarisation, concretisation, compassion move, negative comparison, norm and value violations, self-identity descriptions, negative lexicalisation, victimisation, hyperbole, and warning. The findings show that the discursive strategies deeply related to mental models were used to generate power by polarising Israel as a victim, which can influence the thoughts of news receivers globally. Portraying Israel as a victim bolsters Israel’s positive self-image while simultaneously creating a negative picture of the Hamas organisation. The media’s incessant depiction of Israel as a victim, with a particular emphasis on the psychological conditions of Israelis, could potentially shape a widespread perception and collective understanding of the country as being victimised. By providing insights into the discursive construction of terrorists and victims, this study is hoped to contribute to a greater understanding of how media discourse constructs identities.